1264. Durability and effectiveness of fostemsavir in heavily treatment-experienced people with HIV. (15th December 2022) - Hsu, Ricky K; Brunet, Laurence; Fusco, Jennifer S; Henegar, Cassidy; Vannappagari, Vani; Clark, Andrew; Lackey, Philip C; Pierone, Gerald; Fusco, Gregory P
Abstract: Background: Paired with other active antiretrovirals (ARVs), fostemsavir (FTR) may offer heavily treatment-experienced (HTE) people with HIV (PWH) options for continuing effective treatment. Durability and effectiveness of FTR-containing regimens in routine clinical care in the United States were assessed. Methods: Electronic health record data from the OPERA ® cohort were used to identify adults initiating FTR-containing regimens between 2JUL2020 (FDA approval) and 1SEP2021. Eligible PWH were followed from first FTR prescription (baseline) until FTR discontinuation, death, loss to follow up, or study end (28FEB2022). Durability was assessed as frequency of FTR discontinuation. Virologic outcomes assessed at 6 and 12 months (±3 months) included suppression (viral load [VL] < 50 copies/mL), virologic failure (2 consecutive VL ≥200 copies/mL or 1 VL ≥200 copies/mL + FTR discontinuation within 120 days after suppression), and viral blips (1 VL ≥50 copies/mL preceded and followed by VLs < 50 copies/mL). Analyses were stratified by baseline viral load (bVL < 50 copies/mL; bVL ≥50 copies/mL). Results: Overall, 86 PWH initiated FTR (bVL < 50: 30; bVL ≥50: 55), with median follow up of 10.8 months (IQR: 6.8, 15.3). Compared to PWH with bVL ≥50, those with bVL < 50 were older and more likely to be white and have lived longer with HIV (Table 1). Over follow up, 20% discontinued FTR (Table 2). Most (82%) FTR discontinuations were switches to alternative regimens; the remaining were ARV interruptions (no ARVs for > 45 days). Among PWH with bVL < 50, most maintained suppression (6 months: 74%; 12 months: 82%; Figure). Among PWH with bVL ≥50 and with follow up VL during the period assessed, 33% were suppressed at 6 months, 36% were suppressed at 12 months, and 48% achieved suppression at any time over the entire follow up (Figure). In either group, ≤5 PWH experienced virologic failure or blip, though the proportion of PWH with multiple follow up VLs was low. Conclusion: Despite a heterogenous population and diverse regimens, most HTE PWH remained on FTR at study end. Most PWH with bVL < 50 remained suppressed and half of PWH with bVL ≥50 achieved suppression over the entire study period. Virologic failure and blips were infrequent, although follow up was limited in this early evaluation of real-world FTR use. Disclosures: Ricky K. Hsu, MD, Gilead: Honoraria|Merck: Honoraria|ViiV: Advisor/Consultant|ViiV: Grant/Research Support|ViiV: Honoraria Laurence Brunet, PhD, AIDS Healthcare Foundation: Client of my employer|EMD Serono: Client of my employer|Gilead Sciences: Client of my employer|Janssen: Client of my employer|Merck & Co: Client of my employer|TheraTechnologies: Client of my employer|ViiV Healthcare: Client of my employer Jennifer S. Fusco, BS, AIDS Healthcare Foundation: Client of my employer|EMD Serono: Client of my employer|Gilead Sciences: Client of my employer|Janssen: Client of my employer|Merck & Co.: Client of my employer|TheraTechnologies: Client of my employer|ViiV Healthcare: Client of my employer Cassidy Henegar, PhD, MSPH, GlaxoSmithKline: Stocks/Bonds|ViiV Healthcare: full-time employee Vani Vannappagari, MBBS, MPH, PhD, ViiV Healthcare: I am full time employee of ViiV Healthcare and receive GlaxoSmithKline stock as part of my compensation package|ViiV Healthcare: Stocks/Bonds Andrew Clark, MD, ViiV Healthcare: Employee|ViiV Healthcare: Stocks/Bonds Gerald Pierone, Jr., MD, Gilead: Grant/Research Support|GSK-VIIV: Grant/Research Support Gregory P. Fusco, MD, MPH, AIDS Healthcare Foundation: Client of employer|EMD: Grant/Research Support|Gilead Sciences: Client of employer|Janssen: Client of employer|Merck & Co.: Client of employer|Theratechnologies: Client of employer|ViiV Healthcare: Client of employer.